The Impact of Impending Demolition on Ageing in Place in Declining Neighbourhoods in Shenyang, China - Li, Xin; van Ham, Maarten; Kleinhans, Reinout; Zhang, Pingyu (A+BE | Architecture and the Built Environment, 2018)
Facilitating ageing in place enables older people to remain in familiar places, namely their homes and neighbourhoods, as long as possible. However, urban redevelopment that includes the forced relocation of residents often makes ageing in place impossible. The present research examined how impending neighbourhood demolition affects the ageing in place of older people in Shenyang, China. Starting with the presscompetence model and related academic work concerning the influences of person– environment interaction on the wellbeing of older people, this paper discusses the impact of forced relocation and demolition on the meaning of home, the living arrangement and the role of family, and strategies to maintain the independence of older people. Transcript analysis of 54 semi-structured interviews with older residents revealed their ambivalent feelings towards the impending demolition. Long-term residence in declining neighbourhoods makes them feel rooted and enables them to develop their living strategies and plan for ageing in place. However, neighbourhood decline challenges their daily activities and they increasingly struggle to maintain their independence, which leads them to consider impending neighbourhood redevelopment as an opportunity to improve their living conditions. The impending forced relocation interrupts their place-based identity and living strategies and causes significant stress due to their lack of autonomy in the decision making on the relocation process, the move itself and their uncertainty regarding their post-relocation life. Implications for further research and policy are provided.